Application of an Electronic Nose Technology for the Prediction of Chemical Process Contaminants in Roasted Almonds - Marta Mesías; Juan Diego Barea-Ramos; Jesús Lozano; Francisco J. Morales; Daniel Martín-Vertedor (Chemosensors, 2023)
The purpose of this study was to investigate the use of an experimental electronic nose (E-nose) as a predictive tool for detecting the formation of chemical process contaminants in roasted almonds. Whole and ground almonds were subjected to different thermal treatments, and the levels of acrylamide, hydroxymethylfurfural (HMF) and furfural were analysed. Subsequently, the aromas were detected by using the electronic device. Roasted almonds were classified as positive or negative sensory attributes by a tasting panel. Positive aromas were related to the intensity of the almond odour and the roasted aroma, whereas negative ones were linked to a burnt smell resulting from high-intensity thermal treatments. The electronic signals obtained by the E-nose were correlated with the content of acrylamide, HMF, and furfural (<semantics><msubsup>RCV2</msubsup></semantics> > 0.83; <semantics><msubsup>RP2</msubsup></semantics> > 0.76 in whole roasted almonds; <semantics><msubsup>RCV2</msubsup> </semantics> > 0.88; <semantics><msubsup>RP 2</msubsup></semantics> > 0.95 in ground roasted almonds). This suggest that the E-nose can predict the presence of these contaminants in roasted almonds. In conclusion, the E-nose may be a useful device to evaluate the quality of roasted foods based on their sensory characteristics but also their safety in terms of the content of harmful compounds, making it a useful predictive chemometric tool for assessing the formation of contaminants during almond processing.